The women of Chateau Lafayette [large type] - Dray, Stephanie (Thorndike Press large print basic series., 2021)
"1774. Gently bred noblewoman Adrienne Lafayette must renounce the complicated man she loves, or risk her life for a legacy that will inspire generations to come. 1914. Glittering New York socialite Beatrice Chanler witnesses the devastation of the war in France firsthand, and must convince America to fight for what's right. 1940. French schoolteacher and aspiring artist Marthe Simone makes a discovery that calls into question who she is, and more importantly, who she is willing to become. The Women of Chateau Lafayette is a sweeping novel about duty and hope, love and courage, and the strength we take from those who came before us"--Page 4 of cover.